Worthy of the cause for which they fight : the Civil War diary of Brigadier General Daniel Harris Reynolds, 1861-1865 - Reynolds, Daniel Harris, 1832-1902 (Civil War in the West., 2011)
Robert Patrick Bender is a history instructor at Eastern New Mexico University-Roswell. He is the author of Like Grass Before the Scythe: The Life and Death of Sgt. William Remmel, 121st New York Infantry.